Bovine endometrial cells do not mount an inflammatory response to Leptospira. Issue 3 (4th August 2021) - Molinari, Paula C C; Nally, Jarlath E; Bromfield, John J
Abstract : Leptospirosis causes abortion, premature birth, and stillbirth in cattle, but the mechanisms remain unclear. Infected cattle shed Leptospira intermittently and present a range of clinical symptoms, making diagnosis difficult. The primary route of Leptospira transmission in any animal is the colonization of the renal tubule and excretion by urine; however, Leptospira can also colonize the female reproductive tract of cows and can be transmitted by semen. Vaccination against Leptospira in the US is routine in cattle, but immunity is not guaranteed. The cell wall of Leptospira contains toll-like receptor agonists including peptidoglycan and lipopolysaccharide. The capacity of Leptospira to initiate an innate inflammatory response from uterine endometrial cells is unknown but may be a cause of reproductive failure. Using cell culture, we tested the capacity of bovine endometrial epithelial cells or human monocytes to elicit an inflammatory response to Leptospira borgpetersenii serovar Hardjo strain TC273. Cells were exposed to either heat-killed Leptospira, Leptospira outer membrane, Escherichia coli lipopolysaccharide, Pam3CSK4 or medium alone for 2 to 24 h. Exposure of bovine endometrial epithelial cells or human monocytes to heat-killed Leptospira or Leptospira outer membrane did not induce the expression of IL1A, IL1B, IL6, or CXCL8, while exposure to E. coli lipopolysaccharide or Pam3CSK4 increased the expression of IL1A, IL1B, IL6, and CXCL8 compared to control cells. This data suggest that Leptospira does not trigger a classical inflammatory response in endometrial cells. Understanding the interaction between Leptospira and the female reproductive tract is important in determining the mechanisms of Leptospirosis associated with reproductive failure. Lay summary: Cows infected with the Leptospira have abortion and stillbirth. It is not known how Leptospira causes pregnancy failure in the cow. We tested if Leptospira causes inflammation in cells of the uterus which triggers pregnancy failure. We collected cells from the uterus of healthy cows at the abattoir and placed them into culture with Leptospira and measured the expression of genes associated with inflammation. To our surprise, cells of the uterus did not respond to Leptospira ; however, the same cells did respond to other disease-causing bacteria found in the uterus. This suggests that cells of the uterus can recognize bacteria and produce an inflammatory reaction but not in response to Leptospira . This finding suggests the immune system of the uterus cannot detect Leptospira which may go on to cause reproductive failure in cows. Understanding how Leptospira interact with cells of the uterus will help reduce pregnancy failure of cows with leptospirosis.